Interface‐Controlled Biomimetic Intrafibrillar Mineralization of Collagen: Effect of Ca2+/[PO4]3− Concentration Ratio - Urasawadee Amornkitbamrung; Yongjae In; Jung Heon Lee; Zhen Wang; Sang Ho Oh; Heungsoo Shin; Dae Sung Yoon; Hyunjung Shin (Advanced Materials Interfaces, 2023)
Abstract Mineralized fibrils are important building blocks in bone tissue, formed by the hierarchical assembly of collagen molecules and crystalline hydroxyapatite (HAp). The mineralization pathway of HAp is reported as a nonclassical‐crystallization, but the nanoconfined crystallization in collagen fibrils remains poorly understood. The mechanism of intrafibrillar mineralization of collagen‐PDA fibrils in modified‐simulated body fluid (m‐SBF) solution is studied. Collagen‐amorphous calcium phosphate (ACP) fibrils are obtained by assembling collagen‐PDA fibrils with polyaspartic acid (pAsp) as a stabilizer. The ACP undergoes a phase transformation to HAp within the fibrils upon adjusting the phosphate concentration. It is found that the phase transformation of ACP to HAp in collagen fibrils can be accelerated with a 12 h incubation with 1/10 ratio of Ca2+ to [PO4]3−. A lower ratio of 1/1 and 1/5 results in a much slower phase transformation. This finding suggests that an elevated concentration of [PO4]3− is crucial for faster phase transformation. The relationship between the crystallization rate of HAp in the fibrils and the degree of mineralization is found to be linear in all cases, indicating an interface‐controlled process. This gives a better understanding of the mechanism of HAp mineralization in collagen fibrils, providing an effective approach to material design.